Pictorial Atlas of Fossil and Extant Horseshoe Crabs, With Focus on Xiphosurida - Bicknell, Russell D. C.; Pates, Stephen (Frontiers in Earth Science, 2020)
Horseshoe crabs are an iconic group of extant chelicerates, with a stunning fossil record that extends to at least the Lower Ordovician (~480 million years ago). As such, the group has retained significant biological and palaeontological interest. The sporadic nature of descriptive and systematic research into fossil horseshoe crabs over the last two centuries has spread information on the group across more than 200 texts dating from the early nineteenth century to the present day. We present the most comprehensive pictorial atlas of horseshoe crabs to date to pool these important data together. This review highlights taxa such as Bellinurus lacoei and Limulus priscus that have never been documented with photography. Furthermore, key morphological features of the true horseshoe crab (Xiphosurida) families—Austrolimulidae, Belinuridae, Limulidae, Paleolimulidae, and Rolfeiidae—are described. The evolutionary history of horseshoe crabs is reviewed and the current issues facing any possible biogeographic work are presented. Four major future directions that should be adopted by horseshoe crab researchers are outlined. We conclude that this review provides the basis for innovative geographic and geometric morphometric studies needed to uncover facets of horseshoe crab evolution.